P184 Candida auris candidemia in COVID-19 and post-COVID-19 patients in a tertiary care hospital in North India. (20th September 2022) - Dixit, Ajai Kumar; Marak, Rungmei S. K.; Bhartiya, Chitra; Azim, Afzal; Sahu, Chinmoy; Tripathi, Shikha
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Introduction: Candida spp. accounts for 70%-80% of invasive bloodstream fungal infections. It is most commonly spread in long-term care facilities, caring for people with severe medical conditions. Patients hospitalized for COVID-19 are at risk for healthcare-associated infections like candidemia. Candida auris is an emerging, multidrug-resistant, healthcare-associated fungal pathogen. Candida auris is currently one of the most common clinical fungal pathogens, causing nosocomial infections. Due to its higher drug-resistance rate, C. auris is more difficult to treat, requires longer hospitalization periods, and results in higher morbidity and mortality than other Candida species. Aim and Objectives: To analyze the risk factors associated with C. auris candidemia in COVID-19 and post-COVID-19 patients at tertiary care center. Material and Methods: We prospectively analyzed all positive blood samples which were received in the Microbiology department at SGPGI, Lucknow for a period of 1 year (March 2020-March 2021). Blood samples were inoculated and cultured in BACTEC Bottles (BD) and incubated for 5 days at 37° C. The bottles which flagged positive, a Gram's stain was performed and were sub-cultured on SDA for isolation of yeast colonies. Isolated yeasts were identified by phenotypic method and confirmed by MALDI-TOF MS. Demographics details of the patients were collected and recorded. The significant associated risk factors with C. auris candidemia were analyzed. Results: A total of 13 000 blood samples were received during the 1-year study period from different departments of the hospital.1.25% ( n  = 163) of the blood culture samples were positive for candidemia. Out of 163 Candida culture-positive blood samples, 27.61% ( n  = 45) were C. auris . A total of 64% ( n  = 29) C. auris candidemia was seen in non-COVID-19 patients, 31.1% ( n  = 14) in COVID-19 patients, and two patients had a history of post-COVID-19 infection. The associated risk factors included the use of broad-spectrum antibiotics, intravenous catheterization, underlying respiratory illness, mechanical ventilation, use of steroids, and dialysis. A total of 46.6% ( n  = 21) mortality was seen with C. auris candidemia. Conclusions: Candida auris candidemia continues to be a threat in hospitalized patients. This study shows prevalence of C. auris candidemia in COVID-19 and post-COVID-19 patients with 47% mortality. Candida auris is continuously reported from different departments in our institute, especially from intensive care units with high morbidity and mortality. An alertness, awareness and infection control practices by the healthcare personnel will help in early diagnosis and appropriate antifungal therapy and control the spread of C. auris .